The finding of hydrogen trapping at phase boundary in austenitic stainless steel by scanning Kelvin probe force microscopy. (15th March 2019) - Hua, Zhengli; Zhu, Shengyi; An, Bai; Iijima, Takashi; Gu, Chaohua; Zheng, Jinyang
Abstract: Scanning Kelvin probe force microscopy (SKPFM) in nitrogen atmosphere, which can detect the variation of surface contact potential difference (CPD) caused by hydrogen ingress, was used to investigate hydrogen distribution in thermally hydrogen-precharged austenitic stainless steel with strain-induced martensite. Furthermore, the evolutions of hydrogen concentrations in lattice and trapping site are calculated by McNabb–Foster model. Results show that work function of the material is decreased by hydrogen. Hydrogen concentration evolution simulated by the model is consistent with that measured by SKPFM. Particularly, hydrogen is proved to be trapped at the phase boundary between austenite and martensite by SKPFM. Graphical abstract: Unlabelled Image